Single versus multiple drug regimen in epilepsy management: assessment of health-related quality of life outcomes / Lua Pel Lin, Getrude Cosmas and Nurul Hudani Md. Nawi - Lua, Pel Lin; Getrude, Cosmas; Md. Nawi, Nurul Hudani (Institute of Quality and Knowledge Advancement (InQKA) and University Publication Centre (UPENA), 2007)
The importance of health-related quality of life (HRQoL) assessment in epilepsy is justified by potential adverse drug reactions and disease-related psychosocial impacts. This study aims 1) to compare HRQoL outcomes between single and multiple drug regimen and 2) to determine the correlation of HRQoL domain and Total QoL Score. Twenty-two out of 30 eligible out-patients were recruited from a Malaysian public hospital (response rate = 73.3.%). Following written consents, the Malay Quality of Life In Epilepsy -31 (QOLIE-31) instrument was administered (domains: Seizure Worry, Overall Qol, Emotional Well-Being, Energy/Fatigue, Cognitive Functioning, Medication Effects and Social Functioning). Respondents ranged from 18-49 years (mean age= 30; male=9; unmarried-16, jobless = 12). The most commonly-prescribed epilepsy medications were carbamazepine (n=14), sodium valproate (n=ll) and lamotrigine (n=7). Nine participants were on a single drug (Group A) while 11 patients were prescribed > 1 drug (Group B) (missing=2). Results showed that Group A patients produced better scores in all HRQoL domains (except Seizure Worry and Social Functioning) compared to Group B (significant for Emotional Well- Being; p=0.041). The Cognitive Functioning domain correlated ignificantly strongest with Total QoL Score (rs = 0.844). These outcomes indicate that prescribing multiple drugs for epilepsy do not necessarily improve HRQoL and patients strongly associated their cognitive functioning to total QoL. Such information would enhance healthcare professionals' awareness towards HRQoL and could guide prescribing pattern for epilepsy drugs. Nevertheless, other confounding variables required consideration and a larger sample size is needed to generate a more concrete conclusion in future.